National Survey of Weapon-Related Experiences, Behaviors, and Concerns of High School Youth in the United States, 1996 - Sheley, Joseph F. ([Verlag nicht ermittelbar], 2000)
This national-level survey of youth was undertaken to gather detailed behavioral and attitudinal data concerning weapons and violence. The research project sought to obtain information from a broad sample of high-school-aged youth to achieve diversity regarding history, cultural background, population size and density, urban and non-urban mix, economic situation, and class, race, and ethnic distributions. Data for the study were derived from two surveys conducted during the spring of 1996. The first survey was a lengthy questionnaire that focused on exposure to weapons (primarily firearms and knives) and violence, and was completed by 733 10th- and 11th-grade male students. Detail was gathered on all weapon-related incidents up to 12 months prior to the survey. The second survey, consisting of a questionnaire completed by 48 administrators of the 53 schools that the students attended, provided information regarding school characteristics, levels of weapon-related activity in the schools, and anti-violence strategies employed by the schools. The student survey covered demographic characteristics of the respondent, family living situations, educational situations and aspirations, drug, criminal, and gang activities, crime- and violence-related characteristics of family and friends, respondent's social and recreational activities, exposure to violence generally, personal victimization history, and possession of and activities relating to firearms and knives. Administrators were asked to provide basic demographic data about their schools and to rate the seriousness of violence, drugs, guns, and other weapons in their institutions. They were asked to provide weapon-related information about the average male junior in their schools as well as to estimate the number of incidents involving types of weapons on school grounds during the past three years. The administrators were also asked to identify, from an extensive list of violence reduction measures, those that were practiced at their schools. Variables are also provided about the type of school, grades taught, enrollment, and size of the community. In addition to the data collected directly from students and school administrators, Census information concerning the cities and towns in which the sampled schools were located was also obtained. Census data include size of the city or town, racial and ethnic population distributions, age, gender, and educational attainment distributions, median household and per capita income distributions, poverty rates, labor force and unemployment rates, and violent and property crime rates.